Smartphone applications for cancer patients; what we know about them? - Roberto Collado-Borrell; Vicente Escudero-Vilaplana; Almudena Ribed-Sánchez; Sara Ibáñez-García; Ana Herranz-Alonso; María Sanjurjo-Sáez (Elsevier, 2016)
Background and objective: one of the groups that can benefit most from healthcare applications, are cancer patients. However, not all applications have a sufficient level of evidence. Our objective is to analyze the characteristics of mobile healthcare applications for cancer patients and know the reliability of their information. Material and methods: a descriptive observational study of mobile apps targeting cancer patients. In November 2014, we searched mobile applications for cancer patients in the App Store (iOS) and Google Play (Android), using the terms "cancer" and "oncology" (English and/or Spanish languages). Applications were downloaded and evaluated. We registered their general characteristics (classification of cancer, last date of actualization, language and others) and their purpose (whether were informative, diagnostic, or preventive purposes) on an Excel® chart. The analysis was completed with an internet search to analyze their scientific evidence. Results: one hundred and sixty six applications were downloaded. 23.5% were destined for breast cancer. 52.4% upgraded their software in the last year. 98.2 % were in English. Most of the applications had more than one purpose. The most frequent were informative (39.8%), diagnostic (38.6%) and preventive (28.3%). 50.6% presented sufficient scientific evidence. Conclusions: there are many benefits that are expected from these applications. However, we detected a lack of validity of the information, as well as lack of update of the data. To prevente these apps from becoming a safety problem rather than a useful tool for patients, regulation should be put in place